Au / ZnGa2O4 / ZnO composite photocatalyst with tandem heterojunction and a method for photocatalytic non-oxidative coupling of CH4

CN118719058BActive Publication Date: 2026-10-16SHAANXI NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410822900.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-25
Publication Date
2026-10-16
Estimated Expiration
2044-06-25

AI Technical Summary

Technical Problem

但是对于这类金属负载单一半导体的催化剂,仍存在着光生载流子分离效率较低,导致光催化NOCM效率低下的问题

Benefits of technology

[0019] ZnO and ZnGa2O4 possess suitable band positions, while Au and ZnO have suitable work functions and electron affinities, allowing them to form S-type heterojunctions and Schottky junctions, respectively. This invention first synthesizes a ZnGa2O4/ZnO composite material with an S-type heterojunction using a one-pot method. Then, Au nanoparticles are selectively loaded onto ZnGa2O4/ZnO via an impregnation-reduction method, establishing a Schottky junction between the Au nanoparticles and ZnO to obtain an Au/ZnGa2O4/ZnO composite photocatalyst with tandem S-type and Schottky junctions. The preparation method of this composite photocatalyst is simple. When used for photocatalytic NOCM reactions, Au acts as the active site for the hydrogen evolution half-reaction, reducing protons to H2. CH4 is activated and oxidized to CH3· and H2 by holes on the VB of ZnGa2O4. + The coupling of CH3· to form C2H6 enables the migration of photogenerated electrons from ZnGa2O4 to Au through the ZnGa2O4/ZnO S-type heterojunction and the Schottky junction between Au/ZnO, greatly promoting photogenerated carrier separation and improving the photocatalytic NOCM efficiency. This invention provides a simple synthesis method for synthesizing tandem double-junction multi-component composite materials, offering a simple and effective way to improve photogenerated carrier separation efficiency and enhance photocatalytic NOCM performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118719058B_ABST
    Figure CN118719058B_ABST
Patent Text Reader

Abstract

The application discloses an Au / ZnGa2O4 / ZnO composite photocatalyst with a series heterojunction and a method for photocatalytic non-oxidative coupling of CH4. The application forms a ZnGa2O4 / ZnO S-type heterojunction through in-situ growth of ZnGa2O4 on ZnO generated in a reaction process by a simple one-pot method, and then selectively loads Au nanoparticles on the ZnGa2O4 / ZnO by an impregnation-reduction method, establishes a Schottky junction between the Au nanoparticles and the ZnO, and obtains the Au / ZnGa2O4 / ZnO composite photocatalyst with the series heterojunction. The catalyst is used for photocatalytic non-oxidative coupling of CH4, and the series of the Au / ZnO Schottky junction to the ZnGa2O4 / ZnO S-type heterojunction on the catalyst provides a channel for efficient separation of photo-generated carriers, significantly improves migration and separation of the photo-generated carriers, and thus improves the efficiency of photocatalytic non-oxidative coupling of CH4.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of photocatalysts for non-oxidative coupling (NOCM) of CH4 in solar photocatalysis, specifically relating to an Au / ZnGa2O4 / ZnO composite photocatalyst with a tandem heterojunction, and a method for applying it to photocatalyze NOCM. Background Technology

[0002] CH4 is an abundant C1 resource, and converting methane into higher hydrocarbon compounds has always been a major challenge in the natural gas chemical and energy chemical industries. Due to the stable tetrahedral structure of CH4, traditional industrial processes typically involve first converting CH4 into syngas (CO + H2) via high-temperature steam reforming, and then using the syngas to synthesize methanol, light olefins, and liquid hydrocarbons. However, this route relies on high temperature and pressure, increasing the complexity and cost of the process. In contrast, CH4 can be converted into higher hydrocarbons through various valuable pathways such as oxidative coupling, non-oxidative coupling, and aromatization. Among these, photocatalytic NOCM (non-oxidative coupling of CH4 and carbon) has attracted considerable attention because it utilizes solar energy to convert CH4 into higher alkanes and H2 under mild conditions, and prevents the over-oxidation of CH4 to CO or CO2 under anaerobic conditions, thus enabling the direct conversion of CH4 into high-value chemicals using renewable energy under green conditions. Many photocatalysts have been reported to be active in such reactions, demonstrating the feasibility of photocatalytic conversion. Developing novel, efficient, and highly selective photocatalysts is a key focus of research on non-oxidative coupling of methane, but challenges remain.

[0003] Catalysts used for photocatalytic NOCM are mostly noble metals (such as Pt, Au, Pd, etc.) supported on single metal oxides (such as ZnO, Ga2O3, TiO2, WO3, etc.) (Nat. Energy 8(2023)1013-1022. Nat. Commun. 13(2022)2806. Energy Environ Sci. 11(2018)294-298. Nat. Commun. 7(2016)12273. Green Chem. 22(2020)4669-4675.). However, for these metal-supported single semiconductor catalysts, there is still a problem of low photogenerated carrier separation efficiency, resulting in low photocatalytic NOCM efficiency. The construction of heterojunctions, element doping, noble metal loading, defect engineering, and morphology control are common methods to improve the separation efficiency of photogenerated carriers in semiconductors. Among them, the construction of reasonable heterojunctions is considered to be one of the most effective means to promote the rapid separation of photogenerated carriers in semiconductors. Summary of the Invention

[0004] The purpose of this invention is to provide an Au / ZnGa2O4 / ZnO composite photocatalyst with a tandem heterojunction, which improves the separation efficiency of photogenerated carriers and thus enhances its performance in photocatalyzing non-oxidative coupling of CH4.

[0005] The Au / ZnGa2O4 / ZnO composite photocatalyst with a tandem heterojunction provided by this invention is prepared by the following method:

[0006] Step 1: Disperse the water-soluble salts of gallium and zinc and hexamethylenetetramine in a mixed solvent of deionized water and anhydrous ethanol, and stir until homogeneous; then transfer the resulting mixture to a reaction vessel lined with polytetrafluoroethylene, and hydrothermally react at 150-170°C for 10-14 hours; after the reaction is complete, collect the product, wash it with anhydrous ethanol and deionized water respectively, and then vacuum dry it.

[0007] Step 2: Grind the dried product from Step 1 and place it in a covered crucible. Calcine it at 350-450℃ for 3-5 hours in air atmosphere to obtain ZnGa2O4 / ZnO composite material.

[0008] Step 3: Disperse the ZnGa2O4 / ZnO composite material in deionized water, add chloroauric acid aqueous solution, stir evenly, then add sodium borohydride aqueous solution, and stir the reaction at room temperature for 25-35 min; after the reaction is completed, collect the product, wash it with anhydrous ethanol and deionized water respectively, and then vacuum dry it to obtain Au / ZnGa2O4 / ZnO composite photocatalyst.

[0009] In step 1 above, the preferred molar ratio of the water-soluble salt of gallium, the water-soluble salt of zinc, and hexamethylenetetramine is 1:5 to 100:4 to 75.

[0010] In step 1 above, preferably, the water-soluble salt of gallium is any one of hydrated gallium nitrate and hydrated gallium sulfate, and the water-soluble salt of zinc is any one of zinc nitrate hexahydrate, zinc acetate dihydrate, and zinc sulfate heptahydrate.

[0011] In step 1 above, the volume ratio of deionized water to anhydrous ethanol in the mixed solvent is preferably 1:1 to 2.

[0012] In step 1 above, it is further preferred to perform a hydrothermal reaction at 160°C for 12 hours.

[0013] In step 2 above, it is further preferred to calcine at 400°C for 4 hours in an air atmosphere.

[0014] In step 3 above, the preferred mass ratio of gold element in chloroauric acid to ZnGa2O4 / ZnO composite material and sodium borohydride is 1:50-400:2-20.

[0015] In the Au / ZnGa2O4 / ZnO composite photocatalyst with tandem heterojunction of the present invention, ZnGa2O4 accounts for 2% to 30% of the mass percentage of ZnGa2O4 / ZnO, and Au accounts for 0.2% to 2.0% of the mass percentage of Au / ZnGa2O4 / ZnO.

[0016] This invention also provides a method for photocatalytic non-oxidative coupling of CH4. The specific method is as follows: the Au / ZnGa2O4 / ZnO composite photocatalyst with tandem heterojunction is drop-coated onto the conductive surface of an FTO plate. After drying, the plate is placed in a photoreaction tube, sealed, and Ar gas is introduced into the reaction tube to remove the air inside. Then, pure CH4 gas is injected, and the plate is irradiated under ultraviolet-visible light for 3 to 5 hours to photocatalyze the generation of C2H6 and H2 from CH4.

[0017] In the above-mentioned photocatalytic non-oxidative coupling method of CH4, the volume ratio of CH4 to Ar is preferably 0.03 to 0.05:1.

[0018] The beneficial effects of this invention are as follows:

[0019] ZnO and ZnGa2O4 possess suitable band positions, while Au and ZnO have suitable work functions and electron affinities, allowing them to form S-type heterojunctions and Schottky junctions, respectively. This invention first synthesizes a ZnGa2O4 / ZnO composite material with an S-type heterojunction using a one-pot method. Then, Au nanoparticles are selectively loaded onto ZnGa2O4 / ZnO via an impregnation-reduction method, establishing a Schottky junction between the Au nanoparticles and ZnO to obtain an Au / ZnGa2O4 / ZnO composite photocatalyst with tandem S-type and Schottky junctions. The preparation method of this composite photocatalyst is simple. When used for photocatalytic NOCM reactions, Au acts as the active site for the hydrogen evolution half-reaction, reducing protons to H2. CH4 is activated and oxidized to CH3· and H2 by holes on the VB of ZnGa2O4. + The coupling of CH3· to form C2H6 enables the migration of photogenerated electrons from ZnGa2O4 to Au through the ZnGa2O4 / ZnO S-type heterojunction and the Schottky junction between Au / ZnO, greatly promoting photogenerated carrier separation and improving the photocatalytic NOCM efficiency. This invention provides a simple synthesis method for synthesizing tandem double-junction multi-component composite materials, offering a simple and effective way to improve photogenerated carrier separation efficiency and enhance photocatalytic NOCM performance. Attached Figure Description

[0020] Figure 1 Au in Example 1 0.75 XRD patterns of ZGO / ZnO-15, ZGO / ZnO-15, ZnO in Comparative Example 1, and ZGO in Comparative Example 2.

[0021] Figure 2 Au in Example 1 0.75 SEM image of / ZGO / ZnO-15.

[0022] Figure 3 Au in Example 1 0.75 TEM(a) and HRTEM(b) plots of / ZGO / ZnO-15.

[0023] Figure 4 Au in Example 1 0.75 UV-Vis diffuse reflectance spectra of ZGO / ZnO-15, ZGO / ZnO-15, ZnO in Comparative Example 1, and ZGO in Comparative Example 2.

[0024] Figure 5 These are the Tauc plots of ZnO in Comparative Example 1 and ZGO in Comparative Example 2.

[0025] Figure 6 The Mott-Schottky diagrams are for ZnO in Comparative Example 1 and ZGO in Comparative Example 2.

[0026] Figure 7 Au in Example 1 0.75 / ZGO / ZnO-15, Au in Comparative Example 1 0.75 / ZnO, Au in Comparative Example 2 0.75 / Comparison of photocatalytic NOCM activity of ZGO under UV-Vis light.

[0027] Figure 8 This is a comparison chart of the photocatalytic NOCM activity of Au / ZGO / ZnO under UV-Vis light at different ZGO contents (mass fraction) in Example 1.

[0028] Figure 9 This is a comparison chart of the photocatalytic NOCM activity of Au / ZGO / ZnO under UV-Vis light at different Au contents (mass fraction) in Example 1. Detailed Implementation

[0029] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments, but the scope of protection of the present invention is not limited to these embodiments.

[0030] Example 1

[0031] Step 1: Weigh 0.102 g (0.4 mmol) Ga(NO3)3·xH2O, 1.18 g (4 mmol) Zn(NO3)2·6H2O, and 0.42 g (3 mmol) HMT, and disperse them in a 1:1 mixture of deionized water and anhydrous ethanol in 60 mL. Stir for 30 min, then transfer the resulting mixture to a 100 mL polytetrafluoroethylene-lined reactor. Place the reactor in an oven and react at 160 °C for 12 h with a heating rate of 5 °C / min. After the reaction is complete, collect the product, wash it three times each with anhydrous ethanol and deionized water, and then dry it in a 60 °C vacuum oven.

[0032] Step 2: Grind the dried product from Step 1 and place it in a covered crucible. Transfer the crucible to a muffle furnace and calcine at 400℃ for 4 hours in air atmosphere, with a heating rate of 4℃ / min, to obtain a white ZnGa2O4 / ZnO composite material. The ZnGa2O4 / ZnO composite material contains 15% ZnGa2O4 by mass, denoted as ZGO / ZnO-15.

[0033] Step 3: Disperse 100 mg ZGO / ZnO-15 in 30 mL of deionized water, then add 156.8 μL of HAuCl4 aqueous solution (concentration: 4.78 mg Au / mL), stir for 30 min, then add 1 mL of freshly prepared 0.132 M NaBH4 aqueous solution, and stir the reaction at room temperature for 30 min. After the reaction is complete, collect the product, wash it three times each with anhydrous ethanol and deionized water, and then dry it in a vacuum oven at 60 °C to obtain a light purple Au-supported ZnGa2O4 / ZnO, i.e., Au / ZnGa2O4 / ZnO composite photocatalyst. The mass fraction of Au in the Au / ZnGa2O4 / ZnO composite photocatalyst is 0.75%, denoted as Au. 0.75 / ZGO / ZnO-15.

[0034] Comparative Example 1

[0035] Step 1: Weigh 1.18 g (4 mmol) Zn(NO3)2·6H2O and 0.42 g (3 mmol) HMT, disperse them in a 1:1 mixture of deionized water and anhydrous ethanol in 60 mL, stir for 30 min, then transfer the resulting mixture to a 100 mL polytetrafluoroethylene-lined reactor. Place the reactor in an oven and react at 160 °C for 12 h with a heating rate of 5 °C / min. After the reaction is complete, collect the product, wash it three times each with anhydrous ethanol and deionized water, and then dry it in a 60 °C vacuum oven.

[0036] Step 2: Grind the dried product from Step 1 and place it in a covered crucible. Transfer it to a muffle furnace and calcine it at 400°C for 4 hours in air atmosphere with a heating rate of 4°C / min to obtain white ZnO.

[0037] Step 3: Disperse 100 mg ZnO in 30 mL of deionized water, then add 156.8 μL of HAuCl4 aqueous solution (concentration: 4.78 mg Au / mL), stir for 30 min, then add 1 mL of freshly prepared 0.132 M NaBH4 aqueous solution, and stir the reaction at room temperature for 30 min. After the reaction is complete, collect the product, wash it three times each with anhydrous ethanol and deionized water, and then dry it in a vacuum oven at 60 °C to obtain light purple Au-supported ZnO, i.e., Au / ZnO composite photocatalyst. The mass fraction of Au in the Au / ZnO is 0.75%, denoted as Au. 0.75 / ZnO.

[0038] Comparative Example 2

[0039] Step 1: Weigh 2.04 g (8 mmol) Ga(NO3)3·xH2O, 1.18 g (4 mmol) Zn(NO3)2·6H2O, and 0.42 g (3 mmol) HMT, and disperse them in a 1:1 mixture of deionized water and anhydrous ethanol. Stir for 30 min, then transfer the resulting mixture to a 100 mL polytetrafluoroethylene-lined reactor. Place the reactor in an oven and react at 160 °C for 12 h at a heating rate of 5 °C / min. After the reaction is complete, collect the product, wash it three times each with anhydrous ethanol and deionized water, and then dry it in a 60 °C vacuum oven.

[0040] Step 2: Grind the dried product from Step 1 and place it in a covered crucible. Transfer it to a muffle furnace and calcine it at 400°C for 4 hours in air atmosphere with a heating rate of 4°C / min to obtain white ZnGa2O4 (denoted as ZGO).

[0041] Step 3: Disperse 100 mg ZnGa₂O₄ in 30 mL of deionized water, then add 156.8 μL of HAuCl₄ aqueous solution (concentration: 4.78 mg Au / mL), stir for 30 min, then add 1 mL of freshly prepared 0.132 M NaBH₄ aqueous solution, and stir the reaction at room temperature for 30 min. After the reaction is complete, collect the product, wash it three times each with anhydrous ethanol and deionized water, and then dry it in a vacuum oven at 60 °C to obtain light purple Au-supported ZnGa₂O₄, i.e., Au / ZnGa₂O₄ composite photocatalyst. The mass fraction of Au in the Au / ZnGa₂O₄ composite photocatalyst is 0.75%, denoted as Au. 0.75 / ZGO.

[0042] The composite photocatalysts prepared in Example 1 and Comparative Examples 1-2 were characterized structurally, and the results are shown in the figure. Figures 1-6 .

[0043] Depend on Figure 1 It can be seen that in Comparative Example 1, the XRD pattern of the sample obtained by adding only the Zn source (Zn(NO3)2·6H2O) without adding the Ga source (Ga(NO3)3·xH2O) only shows the characteristic diffraction peaks of ZnO (PDF#36-1451), without any other impurity peaks. After adding the Ga source (Ga(NO3)3·xH2O), the XRD pattern of the obtained sample shows that ZnGa2O4 has characteristic diffraction peaks located at 2θ=30.3°, 35.7° and 43.4°, respectively, corresponding to the (220), (311) and (400) planes of ZnGa2O4 (PDF#38-1240), indicating the formation of ZGO / ZnO composite material. In Comparative Example 2, when the molar ratio of Ga(NO3)3·xH2O to Zn(NO3)2·6H2O is 2:1, a pure ZGO phase can be obtained, and there are no impurity diffraction peaks. The XRD pattern of the Au / ZGO / ZnO catalyst supported on Au NPs is similar to that of ZGO / ZnO, and no characteristic diffraction peaks of Au were observed. This may be due to the high dispersion and low content of Au nanoparticles.

[0044] Depend on Figure 2 It can be seen that Au in Example 1 0.75 / ZGO / ZnO-15 has a microstructure of stacked porous sieve-like two-dimensional sheet materials, and its surface is rough and uneven with many mesopores.

[0045] Depend on Figure 3 As can be seen from a, Au in Example 1 0.75 / ZGO / ZnO-15 exhibits a porous, sheet-like structure, consistent with SEM results, and Au nanoparticles can be observed to be well dispersed and deposited on the surface of ZGO / ZnO-15. Figure 3 The black dot circled in red. (HRTEM image) Figure 3 In b), lattice fringes with a spacing of 0.248 nm corresponding to the ZnO(101) plane can be clearly seen. Figure 3 b1), the lattice stripes corresponding to the ZGO(220) plane have a lattice spacing of 0.295 nm ( Figure 3 b2), and lattice fringes with a spacing of 0.236 nm belonging to the Au(111) crystal plane. Figure 3 b3). Moreover, ZGO and ZnO are in close contact, and Au nanoparticles are mainly loaded on ZnO.

[0046] Depend on Figure 4It can be seen that the light absorption of the ZGO / ZnO composite material is basically the same as that of ZnO. After loading Au, an absorption peak appeared in the visible light region at around 525nm. This is due to the surface plasmon resonance effect of Au nanoparticles, which proves that Au was successfully loaded onto ZGO / ZnO.

[0047] Depend on Figures 5-6 It can be seen that the band gaps of ZnO and ZGO are 3.13 and 3.96 eV, respectively. The V values ​​of ZnO and ZGO are... CB The V values ​​for ZnO and ZGO are -0.48 and -0.43 V (Vs.NHE), respectively. VB The work functions are 2.65 and 3.53 eV (vs. NHE), respectively. When the two semiconductors come into contact, an internal electric field is formed at the interface due to the different positions of the Fermi levels in ZnO and ZGO. Electrons in the CB of ZGO spontaneously recombine with holes in the VB of ZnO to balance the energy difference caused by the Fermi level, resulting in band bending and forming an S-type heterojunction. The work function of Au is -5.3 eV (vs. vacuum level), and the electron affinity of ZnO is approximately -4.5 eV (vs. vacuum level). Therefore, a Schottky junction can be formed between Au and ZnO when their surfaces are in contact. When ZnO, ZGO, and Au appear at the same interface, the adjacent ternary components will realize the series connection from the Au / ZnO Schottky junction to the ZGO / ZnO S-type heterojunction.

[0048] Example 2

[0049] Weigh out 10mg Au 0.75 / ZGO / ZnO-15 was dispersed in 200 μL of deionized water and sonicated for 30 min to ensure uniform dispersion. This dispersion was then drop-coated onto the conductive surface of a 3 cm × 1 cm FTO plate, which was subsequently dried in a 60°C oven for 4 h. The dried plate was then placed in a photoreaction tube, sealed, and Ar gas was introduced into the tube for 15 min to purge air. Next, 600 μL of pure CH4 gas was injected into the tube using a 1 mL microsyringe. The reaction was then irradiated with a 300W Xe lamp (PLS-SXE300UV, Perfectlight) using UV-Vis light. After 4 h of irradiation, 200 μL of gas was extracted from the reaction tube using a 1 mL microsyringe and injected into a gas chromatograph (Techcomp GC7900) for product detection. Hydrocarbon products such as C2H6 were detected using an FID (Flame Ionization Detector), and H2 was detected using a TCD (Thermal Conductivity Detector). Au was used as a control in Comparative Example 1. 0.75 / ZnO and Au in Comparative Example 2 0.75 / ZGO was used as a photocatalyst in a comparative experiment, and the results are shown below. Figures 7-9 .

[0050] Depend on Figure 7It can be seen that under ultraviolet-visible light, Au in Example 1 0.75 The yields of C2H6 and H2 from / ZGO / ZnO-15 were 12.2 μmol·g. -1 and 10.3 μmol·g -1 The C2H6 production was higher than that of Au in Comparative Examples 1-2. 0.75 / ZnO and Au 0.75 The ZnO and ZGO concentrations increased by 4.5 times and 21.4 times, respectively. This is because the ZnO and ZGO form an S-shaped heterojunction, which effectively promotes the migration of photogenerated charges and inhibits recombination.

[0051] Following the method described in Example 1 above, Au samples with different Au contents and ZnGa2O4 contents were prepared respectively. a / ZGO / ZnO-x (a represents the mass percentage of Au in Au / ZGO / ZnO, a = 0.25%, 0.5%, 0.75%, 1.0%, 1.25%, 1.5%, 1.75%, 2.0%; x represents the mass percentage of ZGO in ZGO / ZnO, x = 2%, 5%, 8%, 11%, 13%, 15%, 21%, 27%), and then the photocatalytic non-oxidative coupling reaction of CH4 was carried out according to the method of Example 2. The results are shown in […]. Figure 8 and Figure 9 .

[0052] Depend on Figure 8 It can be seen that the activity of the samples gradually increases with the increase of ZGO content in the composite photocatalyst, with the sample having the best activity at a theoretical ZGO content of 15%. However, the reaction activity begins to decrease as the ZGO content exceeds 15%. These results indicate that constructing a ZGO / ZnO S-type heterojunction plays a crucial role in improving the reaction activity.

[0053] Depend on Figure 9 It can be seen that when the Au loading is low, the yields of C2H6 and H2 gradually increase with increasing Au content. Optimal activity is achieved at an Au mass fraction of 0.75%. With further increases in Au loading, the C2H6 yield decreases slightly and remains relatively stable.

Claims

1. A method for preparing an Au / ZnGa2O4 / ZnO composite photocatalyst with a tandem heterojunction, characterized in that... The method includes the following steps: Step 1: Disperse the water-soluble salts of gallium and zinc and hexamethylenetetramine in a mixed solvent of deionized water and anhydrous ethanol, and stir until homogeneous; then transfer the resulting mixture to a reaction vessel lined with polytetrafluoroethylene, and hydrothermally react at 150-170℃ for 10-14 h; after the reaction is complete, collect the product, wash it with anhydrous ethanol and deionized water respectively, and then vacuum dry it. Step 2: Grind the dried product from Step 1 and place it in a covered crucible. Calcine it at 350–450°C for 3–5 h in air atmosphere to obtain ZnGa2O4 / ZnO composite material. Step 3: Disperse the ZnGa2O4 / ZnO composite material in deionized water, add chloroauric acid aqueous solution, stir evenly, then add sodium borohydride aqueous solution, and stir the reaction at room temperature for 25-35 min; after the reaction is completed, collect the product, wash it with anhydrous ethanol and deionized water respectively, and then vacuum dry it to obtain Au / ZnGa2O4 / ZnO composite photocatalyst.

2. The preparation method of the Au / ZnGa2O4 / ZnO composite photocatalyst with tandem heterojunction according to claim 1, characterized in that: In step 1, the molar ratio of the water-soluble salt of gallium, the water-soluble salt of zinc, and hexamethylenetetramine is 1:5 to 100:4 to 75.

3. The method for preparing the Au / ZnGa2O4 / ZnO composite photocatalyst with a tandem heterojunction according to claim 1, characterized in that: In step 1, the water-soluble salt of gallium is any one of hydrated gallium nitrate and hydrated gallium sulfate, and the water-soluble salt of zinc is any one of zinc nitrate hexahydrate, zinc acetate dihydrate, and zinc sulfate heptahydrate.

4. The method for preparing the Au / ZnGa2O4 / ZnO composite photocatalyst with a tandem heterojunction according to claim 1, characterized in that: In step 1, the volume ratio of deionized water to anhydrous ethanol in the mixed solvent is 1:1 to 2.

5. The method for preparing the Au / ZnGa2O4 / ZnO composite photocatalyst with a tandem heterojunction according to claim 1, characterized in that: In step 1, the hydrothermal reaction is carried out at 160℃ for 12 h.

6. The method for preparing the Au / ZnGa2O4 / ZnO composite photocatalyst with a tandem heterojunction according to claim 1, characterized in that: In step 2, the sample is calcined at 400°C for 4 hours in an air atmosphere.

7. The method for preparing the Au / ZnGa2O4 / ZnO composite photocatalyst with a tandem heterojunction according to claim 1, characterized in that: In step 3, the mass ratio of gold element in chloroauric acid to ZnGa2O4 / ZnO composite material and sodium borohydride is 1:50-400:2-20.

8. The Au / ZnGa2O4 / ZnO composite photocatalyst with a tandem heterojunction prepared by the method according to any one of claims 1 to 7, wherein ZnGa2O4 accounts for 2% to 30% of the mass percentage of ZnGa2O4 / ZnO, and Au accounts for 0.2% to 2.0% of the mass percentage of Au / ZnGa2O4 / ZnO.

9. A method for photocatalytic non-oxidative coupling of CH4, characterized in that: The Au / ZnGa2O4 / ZnO composite photocatalyst with a tandem heterojunction as described in claim 8 was drop-coated onto the conductive surface of an FTO plate. After drying, the plate was placed in a photocatalytic reaction tube, sealed, and Ar gas was introduced into the reaction tube to remove the air inside. Then, pure CH4 gas was injected, and the plate was irradiated under ultraviolet-visible light for 3–5 h to photocatalyze the generation of C2H6 and H2 from CH4.

10. The method for photocatalytic non-oxidative coupling of CH4 according to claim 9, characterized in that: The volume ratio of CH4 to Ar is 0.03 to 0.05:1.

Citation Information

Patent Citations

  • Preparation and application of porous structure ZnO / ZnGa2O4 visible-light-induced photocatalyst with high specific surface area

    CN105727925A

  • Preparation method of mesoporous P-doped carbon nitride hollow sphere catalyst with Ni2P loaded on inner and outer surfaces simultaneously

    CN115475648A